ANALYSIS OF MSME CHALLENGES AND OPPORTUNITIES IN THE DIGITAL ERA - Dindin Abdurohim (CV. Adiba Aisha Amira, 2025)
The advancement of digital technology has globally transformed the business landscape, including the Micro, Small, and Medium Enterprises (MSMEs) sector. This research aims to analyze the challenges and opportunities faced by MSMEs in the digital era. Key challenges involve limited access and understanding of technology, digital security, and intensifying competition. MSMEs also face risks related to data privacy and regulatory uncertainties in the digital environment. However, amidst these challenges, the digital era presents new opportunities for MSMEs, such as market globalization, product innovation, and operational efficiency through technology integration. Government efforts, business stakeholders, and educational institutions are needed to enhance the digital literacy of MSMEs, provide supportive infrastructure, and develop policies that facilitate MSME growth in the digital era. This research provides profound insights into the dynamics of MSMEs amid technological changes, with the hope of contributing to the development of policies and strategies that support MSME growth in the digital era.